Attitudes of Black Clergy toward Mental Health Professionals: Implications for Pastoral Care - Richardson, Bernard (1989)
Reports on research in which 27 pastors and 81 parishioners in a Michigan city responded to a Semantic Differential instrument in an attempt to measure attitudes of black clergy toward mental health professionals. Statistical analyses suggest that black clergy tend to hold favorable attitudes toward mental health workers, a propensity running counter to some popular notions. Postulates a variety of possible reasons for the finding and urges additional research to guide cooperate efforts of black clergy and mental health professionals in their common desire to foster the social, spiritual, and psychological well-being of persons in the black community.